On the Consistency of the Darken Method with the Onsager Representation for Diffusion in Multicomponent Systems - Zajusz, Marek; Tkacz-Śmiech, Katarzyna; Bożek, Bogusław; Danielewski, Marek (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2016)
A consistency between the Darken method and the Onsager representation for cross diffusion in multicomponent system is shown. The justification is made by defining new sets of forces and fluxes linearly interrelated by a symmetric matrix of phenomenological coefficients. For the first time, the system of the components having various molar volumes is treated in this way. It is shown that the transformation leaves the entropy production unchanged. As an example, the entropy production for interdiffusion in the ternary Co-Fe-Ni diffusion couple is calculated and compared with mixing entropy.